Inflammation and Disintegration of Intestinal Villi in an Experimental Model for Vibrio parahaemolyticus-Induced Diarrhea - Ritchie, Jennifer M.; Rui, Haopeng; Zhou, Xiaohui; Iida, Tetsuya; Kodoma, Toshio; Ito, Susuma; Davis, Brigid M.; Bronson, Roderick T.; Waldor, Matthew K. (PLoS pathogens, 2012)
Vibrio parahaemolyticus is a leading cause of seafood-borne gastroenteritis in many parts of the world, but there is limited knowledge of the pathogenesis of V. parahaemolyticus-induced diarrhea. The absence of an oral infection-based small animal model to study V. parahaemolyticus intestinal colonization and disease has constrained analyses of the course of infection and the factors that mediate it. Here, we demonstrate that infant rabbits oro-gastrically inoculated with V. parahaemolyticus develop severe diarrhea and enteritis, the main clinical and pathologic manifestations of disease in infected individuals. The pathogen principally colonizes the distal small intestine, and this colonization is dependent upon type III secretion system 2. The distal small intestine is also the major site of V. parahaemolyticus-induced tissue damage, reduced epithelial barrier function, and inflammation, suggesting that disease in this region of the gastrointestinal tract accounts for most of the diarrhea that accompanies V. parahaemolyticus infection. Infection appears to proceed through a characteristic sequence of steps that includes remarkable elongation of microvilli and the formation of V. parahaemolyticus-filled cavities within the epithelial surface, and culminates in villus disruption. Both depletion of epithelial cell cytoplasm and epithelial cell extrusion contribute to formation of the cavities in the epithelial surface. V. parahaemolyticus also induces proliferation of epithelial cells and recruitment of inflammatory cells, both of which occur before wide-spread damage to the epithelium is evident. Collectively, our findings suggest that V. parahaemolyticus damages the host intestine and elicits disease via previously undescribed processes and mechanisms.